Karakteristik Mutu Food Grade Grease Ramah Lingkungan Berbahan Baku Minyak Bekas Penggorengan - Assrorudin Assrorudin; Refid Ruhibnur; Rosmalinda Rosmalinda; Tardi Kurniawan; Anto Susanto (Jurnal Teknologi Agro-Industri, 2020)
Food grade grease is a lubricant based on vegetable oils, in its safe use for health, does not pollute the environment so it is very beneficial for the pharmaceutical, animal feed, cosmetics and food industry industries in particular. This study aims to obtain a basic formulation of natural antioxidant ingredients and optimum long storage periods that can produce good and long lasting food grade grease, according to quality standards including: corrosion resistance, dropping point, lubricant texture, and pH . The purpose is more detailed, namely to know (1) the treatment of the percentage of activated charcoal (b / b) on the weight of the material as bleaching material at a temperature of 1050C for 1 hour; (2) the effect of increasing the concentration of natural antioxidant ingredients on food grade grease quality; (3) the best storage period for maintaining quality food grade grease quality; and (4) the interaction between the addition of the concentration of anti-corosit chemicals with the treatment period of storage for 5 days, 10 days and 15 days against the quality of food grade grease. The results of the study show (1). 5% activated charcoal is the best treatment, because it produces FFA values, low water content values ​​and visual appearance (color) with values ​​of 0.22%, 0.12%, and bright yellow, and (2). The treatment of the concentration of natural antioxidant material as much as 10% (A3) and treatment of 10 days storage period (T2) is the best treatment to produce food grade grease quality including corocyte test value, melting point, lubricant texture, and pH respectively: 7.99 ; 83.99; 2.49; and 6.99.